Do Digitalization and Green Entrepreneurship Affect Firm Value of Micro, Small and Medium Enterprises (MSMES)? - Pasca Dwi Putra; Andri Zainal; Khairunnisa Harahap; Ivo Selvia Agusti; Hendra Saputra; Roza Thohiri; Fenny Afrida (Jurnal Administrasi Bisnis, 2025)
The purpose of this study is to examine the potential of digitalization and green entrepreneurship to enhance the value of Micro, Small and Medium Enterprises (MSMEs) in Medan City. The research was conducted with MSMEs in the city of Medan. The study involved 146 respondents. The objective of this study is to test a hypothesis using a structural equation model, with the SmartPLS 3.2.8 application being utilized to facilitate this process. Prior to hypothesis testing, the data must first be subjected to a process of validity and reliability testing. The findings of this study indicate that the implementation of digitalization and green entrepreneurship has the potential to enhance the value of MSMEs. Furthermore, the implementation of green entrepreneurship will motivate companies to adopt digitalization. The implementation of digitalization and green entrepreneurship will assist MSMEs in competing and innovating through the utilization of technology and broader marketing strategies, while also prioritizing environmental protection.